Palem Kuning (Chrysalidocarpus lutescens), Daun Suji (Dracaena deremensis), dan Paku-Pakuan (Nephrolepis exaltata) dalam Menurunkan Kadar Karbon Monoksida (CO) - Morita Sari; Sri Muryani; Abdul Hadi Kadarusno (Sanitasi: Jurnal Kesehatan Lingkungan, 2013)
One possible source of indoor air pollution is gasoline engine of motor vehicle. High carbon monoxide (CO) concentration raises the level of CO Hb in the blood, thus causing health disruptionranging from headache to death. One of the efforts which can be applied to cope the problem isutilizing CO absorber plants such as yellow palm (Chrysalidocarpus lutescens), suji leaves(Dracena deremensis) and ferns (Nephrolepis exaltata). The research was aimed to reveal theability of the three plants in reducing CO concentration, and also to know which plant has thehighest absorbing power. The study was an experiment which employed pre test-post test withcontrol group design, and for each type of plant, there were five replications. Motorcycle engineused in the research as the pollution source was ignited for 30 minutes before the subsequentexhaust gas were exposed in one hour to the experiment room which had the dimension of 3 mlength, 2 m width and 2 m height. The results showed that the decrease of CO concentrationamong the three plants were 76,14 % for Chrysalidocarpus lutescens, 81,18 % for Dracaenaderemensis, and 84,08 % for Nephrolepis exaltata, and the statistical test proved that thosepercentage were significantly different (p < 0,001). Further test, found that ferns (Nephrolepisexaltata) has the highest absorbing capability.